Peaceful Innovation: Personality Analysis by Face Decoder for Empowering of the Department of Women’s Affairs and Family Development - Siripattkitti, Dhanabongkoch; Wattanapradith, Khanthong; Vajirapañño, Phrakhupalad Adisak (วารสารสันติศึกษาปริทรรศน์ มจร, 2024)
The objectives of this research article are twofold: first, to examine the problem situation, requirements, theoretical concepts, and Buddhist principles that support the improvement of leadership potential by analyzing personal images through facial coding of leaders in the Department of Women’s Affairs and Family Institution; Second, to research and propose innovations in the analysis of personal photos using facial coding in order to strengthen the leadership capacity of To achieve these objectives, a mixed-methods strategy was taken, specifically an exploratory sequential design. This entailed conducting in-depth interviews with 15 heads of units from the Department of Women’s Affairs and Family Institution. Holding focus group conversations with 8 specialized experts selected using purposeful sample criteria, conducting experimental training sessions for 24 leaders and networks, and evaluating performance using a leadership potential evaluation. A statistical t-test was performed, along with participant observation and reflective thought. The research findings revealed that various difficulties at the Department of Women’s Affairs and Family Institution must be addressed to increase leadership potential. These include centralized personnel allocation, which causes a mismatch between abilities and tasks, uneven job distribution among leaders, a lack of knowledge of individual differences, and poor leadership communication skills. To overcome these challenges, individuals must engage in self-development, be open to learn, and use their experiences in accordance with current theoretical conceptions. This includes comprehending individual diversity in personal images from Eastern and Western viewpoints, as well as transformative leadership communication and ethics. Furthermore, leadership potential is developed using face coding analysis innovation, which includes a two-day interactive training curriculum and three weeks of leadership development activities. Self-awareness, facial expression decoding for personal image analysis, ethics in leadership communication skill development, usage of facial coding analysis tools (Face Decoder), and leadership for organizational peacebuilding are among the topics covered in the program. The experimental results showed a statistically significant rise in leadership potential enhancement scores using face coding analysis, with the post-experimental mean score significantly higher than the pre-experimental score at a significance threshold of 0.05 (t = -6.57). As a result of the study, the G.R.A.C.E LEADERSHIP COMMUNICATION MODEL and the T.C.P Model were identified as valuable insights for improving leadership communication and competency.